Scenario Planning: Enhancing Employee Engagement In Tax Institutions - Andi Zahira Al Humairoh; Mohammad Syamsul Maarif; I Made Sumertajaya (Eduvest - Journal of Universal Studies, 2025)
This research explores the intersection of employee engagement and scenario planning within tax institutions, emphasizing the importance of a motivated workforce for enhancing organizational effectiveness. The study employs a mixed-methods approach, integrating qualitative and quantitative data collection techniques, including surveys and semi-structured interviews, to assess current levels of employee engagement and the factors influencing them among approximately 360 employees from various tax institutions across Indonesia. The findings reveal that work-life balance contribute significantly to employee disengagement. By implementing scenario planning, tax institutions can proactively address these challenges, fostering a culture of adaptability and resilience. The research identifies key drivers of engagement and develops actionable recommendations for enhancing employee engagement through targeted strategies, such as improving work-life balance and creating a supportive organizational culture. Ultimately, this study aims to develop actionable recommendations for enhancing employee engagement through targeted strategies, ultimately contributing to improved organizational performance and employee satisfaction. The implications of this study extend to public administration, offering valuable insights for policy and practice in the realm of employee engagement within the public sector.